Developing an alternative media for visually impaired audiences: ‘Bioskop Harewos’ Bandung - Karolina, Cut Meutia; Maryani, Eni; Sjuchro, Dian Wardiana (Jurnal Studi Komunikasi, 2021)
Bioskop Harewos is a cinema in the Bandung, West Java, intended for visually impaired audiences. This research focused on efforts to uncover the existence of Bioskop Harewos for the visually impaired and the model of watching films of visually impaired audiences in Bioskop Harewos. The research method was a qualitative case study using several theories and concepts for alternative media. This research collected various data from cinematographers, cinema managers, and Bioskop Harewos team and audiences through interviews. The results showed that Bioskop Harewos is an alternative media for visually impaired audiences in Bandung to watch films in cinemas. Even with the ‘Harewos’ system, the Bioskop Harewos had fulfilled the visually impaired audiences’ demands to watch films in the cinema. The technical limitations of Bioskop Harewos did not reduce the value of entertainment for visually impaired audiences.